EFFECTIVENESS OF THE USE OF MULTIMEDIA-BASED LEARNING MEDIA IN BUILDING CONSTRUCTION COURSES - Masdayaroh Masdayaroh; Tuti Iriani; Rosmawita Saleh (LPPM Universitas Negeri Jakarta, 2022)
This research aims to find out the effectiveness of the use of multimedia-based learning media in building construction courses I. The research method used is quasi experimental with a randomized form of pretest-posttest control group design. Data collection is done with pretest and posttest instruments given to two classes of experiments and controls. The results of this study are derived from the Whitney U-Mann test and the N-gain test, which showed that there was a significant difference between the results of the experimental class learning and the control class, and there was an increase in learning outcomes with intervals of 56%-76% in column material, plate material, window door sill material, ladder material, and roofing materials. As a result, the use of multimedia learning materials in these materials is effective for online learning in building construction courses.